Mechanical, thermal and optical properties of natural rubber films with different types of bifunctional aldehydes as curing agents - Rawiporn Promsung; Yeampon Nakaramontri; Claudia Kummerloewe; Jobish Johns; Norbert Vennemann; Ekwipoo Kalkornsurapranee (eXPRESS Polymer Letters)
A new simple system to vulcanize natural rubber (NR) latex at low temperature (50°C) using different bifunctional aldehydes has been proposed. Bifunctional aldehydes with different number of carbon atoms present in the chemical structure, including glyoxal (GX) with 2 carbon atoms, glutaraldehyde (GA) with 5 carbon atoms and phthaldialdehyde (PA) with 8 carbon atoms were added into natural rubber latex. The mechanical, thermal and optical properties of the crosslinked NR were studied. The formation of crosslinking in the cured NRs was confirmed using infrared spectroscopy (ATR-FTIR). A new absorption peak was found at 1589 cm–1 for ‒NH bending of secondary amine in the case of cured NRs when compared to uncured NR. Universal testing machine (UTM), dynamic mechanical thermal analysis (DMA), thermogravimetric analyzer (TGA) and temperature scanning stress relaxation (TSSR) were employed to study the tensile and thermal properties of cured NRs. Results revealed that the GA cured NR exhibited superior mechanical properties in terms of 100% modulus, tensile strength and hardness up to 2.13, 6.38 MPa and 54.67 Shore A, respectively. Furthermore, GA cured NR showed the highest crosslink density (72.40 mol/m3) and also showed better thermal properties among the different curing systems. The optical properties in terms of transparency of cured NRs were studied. It was noticed that PA cured NR gave more transparency and hence it can be introduced in developing materials for sensor applications.